Analysis of Politeness Maxims on the Youtube Channel: Jess no Limit - Hanni Pahiratunisa; Intan Sari Ramdhani (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Humans are creatures that need each other, to interact humans need language as an intermediary. Speaking well can have a good effect on the other person. Politeness is prioritized which must be instilled in humans. As time goes by, technology is getting more sophisticated, therefore speaking or communicating with other humans can already be done through social media. Especially social media Youtube, there is often interaction between users and viewers. Therefore, the researcher is interested in conducting a study entitled "Analysis of Politeness Maxims in Language on the Jess No Limit Youtube Channel" because the purpose of this research is to describe the form of implementation of politeness maxims in language in Jess No Limit content. The method used in this research is descriptive qualitative. Data collection techniques are carried out by observing and recording and then concluding the data that has been obtained. The instrument used is the internet to access Jess No Limit's Youtube channel, videos that are watched as data, transcript sheets that are useful for recording data that has been watched. The results of this analysis aim to provide information to readers about the forms of the implementation of politeness maxims and for researchers who want to research with different objects